Singlet Oxygen Photophysics in Liquid Solvents: Converging on a Unified Picture - Bregnhøj, Mikkel; Westberg, Michael; Minaev, Boris F; Ogilby, Peter R (Accounts of chemical research, 2017)
Singlet oxygen, O2(a1Δg), the lowest excited electronic state of molecular oxygen, is an omnipresent part of life on earth. It is readily formed through a variety of chemical and photochemical processes, and its unique reactions are important not just as a tool in chemical syntheses but also in processes that range from polymer degradation to signaling in biological cells. For these reasons, O2(a1Δg) has been the subject of intense activity in a broad distribution of scientific fields for the past ∼50 years. The characteristic reactions of O2(a1Δg) kinetically compete with processes that deactivate this excited state to the ground state of oxygen, O2(X3Σg –). Moreover, O2(a1Δg) is ideally monitored using one of these deactivation channels: O2(a1Δg) → O2(X3Σg –) phosphorescence at 1270 nm. Thus, there is ample justification to study and control these competing processes, including those mediated by solvents, and the chemistry community has likewise actively tackled this issue. In themselves, the solvent-mediated radiative and nonradiative transitions between the three lowest-lying electronic states of oxygen [O2(X3Σg –), O2(a1Δg), and O2(b1Σg +)] are relevant to issues at the core of modern chemistry. In the isolated oxygen molecule, these transitions are forbidden by quantum-mechanical selection rules. However, solvent molecules perturb oxygen in such a way as to make these transitions more probable. Most interestingly, the effect of a series of solvents on the O2(X3Σg –)–O2(b1Σg +) transition, for example, can be totally different from the effect of the same series of solvents on the O2(X3Σg –)–O2(a1Δg) transition. Moreover, a given solvent that appreciably increases the probability of a radiative transition generally does not provide a correspondingly viable pathway for nonradiative energy loss, and vice versa. The ∼50 years of experimental work leading to these conclusions were not easy; spectroscopically monitoring such weak and low-energy transitions in time-resolved experiments is challenging. Consequently, results obtained from different laboratories often were not consistent. In turn, attempts to interpret molecular events were often simplistic and/or misguided. However, over the recent past, increasingly accurate experiments have converged on a base of credible data, finally forming a consistent picture of this system that is resonant with theoretical models. The concepts involved encompass a large fraction of chemistry’s fundamental lexicon, e.g., spin–orbit coupling, state mixing, quantum tunneling, electronic-to-vibrational energy transfer, activation barriers, collision complexes, and charge-transfer interactions. In this Account, we provide an explanatory overview of the ways in which a given solvent will perturb the radiative and nonradiative transitions between the O2(X3Σg –), O2(a1Δg), and O2(b1Σg +) states.